A Portable Archive of Luso-Castilian Diplomacy in the Late Middle Ages (Edad Media. Revista de Historia, 2026)
This paper analyses a manuscript recently incorporated into the Portuguese National Archives, composed of 42 unpublished documents related to the negotiations of the Alcáçovas-Toledo treaties between the crowns of Portugal and Castile in 1479–1480. Based on the transcription of the codex, the study examines the material features of the volume, its authorship, custodial history, functions, and contents. It concludes that the manuscript constitutes a diplomatic portable archive with functions of consultation and institutional memory. Its analysis offers new perspectives on Luso-Castilian relations and on the practices of production, organization, and preservation of documentation in the late Middle Ages.
Keywords: Diplomacy; Portable archive; Portugal; Castile; Alcáçovas-Toledo; Terçarias de Moura